2001
DOI: 10.1021/jm001125h
|View full text |Cite
|
Sign up to set email alerts
|

2-N-Acylaminoalkylindoles:  Design and Quantitative Structure−Activity Relationship Studies Leading to MT2-Selective Melatonin Antagonists

Abstract: Several indole analogues of melatonin (MLT) were obtained by moving the MLT side chain from C(3) to C(2) of the indole ring. Binding and in vitro functional assays were performed on cloned human MT1 and MT2 receptors, stably transfected in NIH3T3 cells. Quantitative structure-activity relationship studies showed that 4-methoxy-2-(N-acylaminomethyl)indoles, with a benzyl group in position 1, were selective MT2 antagonists and, in particular, N-[(1-p-chlorobenzyl-4-methoxy-1H-indol-2-yl)methyl]propanamide (12) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 72 publications
4
60
0
1
Order By: Relevance
“…However, the two cited solutions are qualitatively consistent with our previous knowledge and can help the interpretation of some observed SARs. Pose B is consistent with the antagonist behavior of this series and with the lack of influence of the substituent at position 8 on intrinsic activity; in fact, for many series of MLT receptor ligands, [14,31,32] intrinsic activity is strongly affected by the presence of substituents in a position corresponding to position 5 of the indole ring of MLT, and in particular it is enhanced by a methoxy group.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…However, the two cited solutions are qualitatively consistent with our previous knowledge and can help the interpretation of some observed SARs. Pose B is consistent with the antagonist behavior of this series and with the lack of influence of the substituent at position 8 on intrinsic activity; in fact, for many series of MLT receptor ligands, [14,31,32] intrinsic activity is strongly affected by the presence of substituents in a position corresponding to position 5 of the indole ring of MLT, and in particular it is enhanced by a methoxy group.…”
Section: Resultssupporting
confidence: 82%
“…Analytical thin-layer chromatography (TLC) was carried out on Merck silica gel 60 F 254 plates. N-(10,11-dihydro-dibenzoA C H T U N G T R E N N U N G [b,f]thiepin-10-ylmethyl) acetamide (14) was purchased from Specs (The Netherlands). Triacetylcellulose (TAC), with a particle size of 15-25 mm, was purchased from Merck (Darmstadt, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other publications (Wallez et al, 2002;Audinot et al, 2003;Yous et al, 2003) reported selective MT 2 ligands with a benzyl substituent in the 2-position of benzofuran bioisosters (S 24014) or a phenyl substituent in the 3-position of tetrahydronaphthalenic (S 28407) or naphthalenic (S 24773) bioisosteres. Following the same rationale, Spadoni et al (2001) synthesized some melatonin derivatives, 2-acylaminoalkylindoles with a substitution by a benzyl in the 1-position (compound 12), that are selective for the MT 2 receptor type. Two other selective MT 2 ligands have been reported with rigidification of the side chain of melatonin with a piperidine amide chain (GR 128107) or piperazine amide chain (compound 13) (Dubocovich et al, 1997;Mattson et al, 2003).…”
Section: Selective Mt 1 and Mt 2 Melatonin Ligandsmentioning
confidence: 99%
“…In fact, a molecular-modeling study was undertaken to rationalize this result, based on the comparison of the structural features of 1 and of other reference antagonists, like luzindole, 4P-PDOT, and UCM454. Conformational analysis led to some important geometrical similarities between these structurally different compounds [26]. These antagonists are characterized by the presence of a substituent positioned out-of-the-plane of their core nucleus (i.e., the indole ring in luzindole or the tetralin scaffold in 4P-PDOT), and we hypothesized that this substituent conferred selectivity for the MT 2 receptor and led to a reduction of intrinsic activity.…”
mentioning
confidence: 99%